An Overview of Antibiotic Use, Length of Stay, and Amputation Incidents in Diabetic Foot Patients at Cut Meutia Regional Hospital - Debbyousha, Maulina; Bayu Rizaldy, Muhammad; Syifa, Siti (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2025)
Diabetic foot ulcer is a condition of ulceration on the skin surface associated with neuropathy and angiopathy in the lower extremities. Improperly treatment for diabetic foot resulting significant functional and financial consequences for the patient. The purpose of study was to determine and assess an Overview of Antibiotic Use, Length of Stay and Amputation Incidents in Diabetic Foot Patients at Cut Meutia Regional Hospital. This type of research is descriptive research using a purposive sampling method with a cross-sectional approach with a sample size of 55 people using the Slovin formula. Data were processed using the univariate method with the results in the form of characteristics of patients are middle age 45-59 years (42.5%), the most patients were male (57.5%) and the majority of patients were housewives (36.3%). The most common description of antibiotic usage is combination antibiotics (71.3%) with the majority is a combination of cephalosporin and metronidazole (48.8%). The most commonly prescribed single antibiotics are cephalosporins (25%). Meanwhile, the length of stay was <7 days (55%) and the majority of patients did not experience amputation (76.3%). The conclusion of this study was the majority of patients were men, middle age 45-59 years, the majority of occupations were housewives, The use of antibiotics was dominated by a combination of cephalosporins with metronidazole and the single antibiotic used was a cephalosporin, the length of stay was <7 days, and the patients did not experience amputation. Keywords: diabetic ulcer, antibiotics, combination therapy, complication